Exploring The Potential of Non-Formal Education for The Development of Human Capital in India - Islahi, Fatima; Nasrin, Nasrin (Journal of Nonformal Education, 2022)
The purpose of this paper is to present a broad overview of the influence of non-formal education on income generation by analysing the relevant literature of recent times. Reports and articles published in key journals from the concerned field, closely defined by their objective of providing skills for economic and social development and the satisfaction of basic needs, were extensively reviewed and analysed. The paper discusses the expanding boundaries of non-formal education, its influence on human resource development, and the constraints to achieving sustainable development. Suggestions for improvement by various research studies have also been examined. The outcome of this analysis has significant consequences for non-formal education stakeholders, instructional planners, and policymakers, as they can aid in the visualisation, prioritisation, and planning of such programmes.